2020
DOI: 10.1101/2020.01.30.20018432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Family-based genome-wide association study of leprosy in Vietnam

Abstract: 1Leprosy is a chronic infectious disease of the skin and peripheral nerves with a strong genetic 2 2 3 1 independently associated SNPs, two located in the HLA class I region (rs1265048: OR=0.69 3 2 [0.58-0.80], combined p-value = 5.53x10 -11 ; and rs114598080: OR=1.47 [1.46-1.48], 3 3 combined p-value = 8.77x10 -13 ), and one located in the HLA class II region (rs3187964 3 4 (OR=1.67 [1.55-1.80], combined p-value = 8.35x10 -16 ). We also validated two previously 3 5 identified risk factors for leprosy: the mis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…These two alleles are tagging an extended haplotype which spans from HLA-A to HLA-DPB1 , a distance of approximately 3.15 Mb (signal #1 in Fig 1 ). These findings are strongly supported by a study of three Indian leprosy cohorts and our family-based leprosy GWAS in Vietnam [ 5 , 7 ]. In the Indian population samples, the authors reported a strong risk effect for leprosy of MHC class II SNP rs1071630 in two case-control samples from New Delhi and Kolkata [ 5 ].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…These two alleles are tagging an extended haplotype which spans from HLA-A to HLA-DPB1 , a distance of approximately 3.15 Mb (signal #1 in Fig 1 ). These findings are strongly supported by a study of three Indian leprosy cohorts and our family-based leprosy GWAS in Vietnam [ 5 , 7 ]. In the Indian population samples, the authors reported a strong risk effect for leprosy of MHC class II SNP rs1071630 in two case-control samples from New Delhi and Kolkata [ 5 ].…”
Section: Discussionsupporting
confidence: 86%
“…The MHC region has been consistently identified as chromosomal location of strong genetic leprosy risk factors, including in our recent Vietnamese GWAS where three independent association signals were identified in the MHC region [ 7 ]. While genetic studies have implicated non-classical MHC genes like LTA and MICA in leprosy susceptibility, the main effects have been assigned to classical class I and class II HLA genes [ 11 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations